3D flower-like defected MoS2 magnetron-sputtered on candle soot for enhanced hydrogen evolution reaction - Gao, Bo; Du, Xiaoye; Ma, Yaming; Li, Yixue; Li, Yanhuai; Ding, Shujiang; Song, Zhongxiao; Xiao, Chunhui (Applied catalysis. B, Environmental, 2020)
3D flower-like1T-2H phase mixed and defected MoS2 is synthesized by RF Magnetron Sputtering which possesses high electrocatalytic efficiency. [Display omitted] •3D flower-like MoS2 with candle soot as template synthesized by Magnetron Sputtering.•1T-2H phase mixed and defected MoS2 can be obtained by a facile method.•MoS2+CS + NF composite shows excellent catalytic performance and durability. Exploring highly efficient, cost-effective and stable electrocatalysts for hydrogen evolution reaction (HER) based on naturally abundant elements is of great interest but still a challenge. As is generally known, molybdenum disulfide (MoS2) represents a promising catalyst to replace the state of the-art platinum (Pt) for HER, but an effective way of applying it is yet unknown due to a significant resistance between basal planes. Herein, for the first time, a novel nanostructure with three-dimensional (3D) flower-like defected MoS2 nanosheets grown directly on candle soot by magnetron sputtering with Ni foam as a supporter was developed, and it displayed excellent catalytic activity and stability. On the one hand, the bombardment of Ar ions in the deposition system could effectively etch the inert basal plane, leading to the formation of defects and steps to increase the active edge sites. On the other hand, the resistance of MoS2-based electrocatalysts decreased due to the unique topographic structure and the existence of 1T-MoS2 phase, and also the composite was superhydrophilic which is beneficial to the contact of the solid-liquid interface. The as-prepared 3D MoS2/candle soot/Ni foam (NF + CS + MoS2) composite has an overpotential of 56 mV at the current density of 10 mA cm−2 and a small Tafel slope of 49 mV decade-1. This present work provides new insight into the large-scale production of chemically active MoS2-based catalysts for HER.